Permasalahan Kesehatan Mental di Masa Covid-19 - Athiyyah; Santoso, Harri (Jurnal Riset dan Pengabdian Masyarakat, 2021)
The beginning of 2020 was the year when people recognized a terrible virus which is now known as Corona Virus Disease 2019 (COVID-19). The length of time that Covid-19 attacks the health of even the lives of people in the world cause changes in normal human life patterns. These changes bring an impact on human mental well-being because they have to experience the detrimental effects caused by the virus. This article aims to describe the mental health problems that occurred during the Covid-19 period and ways to maintain mental health during this pandemic. The technique used is library research by collecting several previous articles. Thus, the results obtained indicate that mental health problems that exist in society are panic buying, anxiety, stress, fear, depression, toxic masculinity, drug and alcohol abuse, psychosomatic disorders, etc. Ways to maintain mental health and prevent it from problems include consuming nutritious foods, building good relationships with family and friends, doing meditation to control anxiety, wisely sorting information, asking for professional help, and so on.